Gastroprotective Potential of Hantap Leaves (Sterculia coccinea Jack) Extract in Stress-Induced Gastric Ulcers of Male White Rats - Yuliet - Yuliet; Khildah Khaerati; Gladies Melinda Lokong (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2024)
Stomach ulcer is a prevalent digestive problem that can lead to serious complications such as bleeding in the digestive tract, perforation, recurrence, cancer, and even death. One of its potential remedies lies in the antioxidant compounds contained in hantap leaves. Accordingly, this study aimed to investigate the anti-gastric ulcer effects of hantap leaf extract in white male rats induced by water immersion and cold-resistant stress methods. Hantap leaf extract (EEDH) was obtained by maceration using 96% ethanol, resulting in a yield of 7.8%. The results of gastric macroscopic observations based on percentage of ulcer inhibition showed that EEDH doses of 50, 100, and 200 mg/kg BW did not have a significant difference (p0.05) with ranitidine, exhibiting the same gastroprotective effects. An increase in the dose does not lead to a corresponding rise in the gastroprotective effect. Therefore, 50 mg/kg BW of EEDH was considered to be the optimum dose.